Epidemiology of MDR Infections in the ICU: Comparing Outcomes in Patients with and Without Prior Antibiotic Exposure - Nasir, Farhina; Firdous, Nuzhat; Afridi, Saleha; Mustafa, Roohana; Mahmood, Khalid; Younus, Rakhshinda (Journal of Neonatal Surgery, 2025)
Background: The significant challenge in Intensive Care Units (ICUs) are so-called multidrug-resistant (MDR) infections, which can cause higher morbidity, longer hospitals stays and high emission costs. The impact of prior antibiotic exposure as a risk factor of the development of MDR organisms is widely recognized but patient outcome is still controversial. Objective: The trial was designed to compare the clinical outcomes of patients with MDR infection in the ICU according to the history of previous exposure to antibiotics. Methods: The study was an observational study conducted over a period of 8 months; January-August 2023, in Medical, and Surgical ICU units of Mayo Hospital, Lahore. Three hundred and twenty patient developing culture-confirmed MDR infections 48 hours or later of ICU admission were included. They categorized patients into two groups depending on recorded system antibiotics utilization within 90 days prior ICU. Clinical/demographic parameters have been examined and multivariate logistic regression was done to assess independent predictors of mortality. Result: A total of 176/320 (55.0%) patients had the history of previous antibiotic exposure. The incidences of diabetes (48.9% vs. 36.1%, p=.3, CKD (35.2% vs. 24.3%, p=.2, thrombocytopenia (30.7%vs.18.8%, p=0.01) and prolonged ICU stay (10 vs. 7 days, p=4) were high among these patients. Yet, the previous exposure to antibiotics was not an independent predictor of death (OR=110p=058). Rather, lengthy mechanical ventilation, prolonged ICU stay and indwelling lines were substantial predictors. Conclusion: While prior antibiotic exposure is associated with increased morbidity and longer hospital stays, it does not independently increase mortality risk in ICU patients with MDR infections.